A complete Raman study of common acid red dyes: application to the identification of artistic materials in polychrome prints. (8th February 2017) - Cesaratto, Anna; Centeno, Silvia A.; Lombardi, John R.; Shibayama, Nobuko; Leona, Marco
Abstract : In this work, we present a complete Raman investigation of a class of compounds that has not received great attention yet, the red naphthol‐based azo dyes. We selected a group of red azo dyes often used by artists in inks and lake pigments: acid red 1, acid red 14, acid red 18, acid red 26, acid red 27, and acid red 73. A set of reference materials was studied by dispersive Raman, FT‐Raman, and surface‐enhanced Raman spectroscopy. The reference spectra were used in the study of late 19th century Japanese polychrome woodblock prints. The azo dyes selected for this study generally gave good Raman spectra at all excitation wavelengths. The results obtained by the various Raman techniques are compared, and the main difficulties in the identification of the compounds in works of art are illustrated and discussed. The fluorescence coming from the matrix in which the colorants are embedded can obscure their Raman signal. For this reason, the advantages and drawbacks of surface‐enhanced Raman spectroscopy with non‐sampling extraction of the colorants have been evaluated. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A complete Raman study of the most common red naphthol‐based azo dyes used as artist materials is presented. The best conditions for their study by Raman spectroscopy on polychrome prints are evaluated and discussed. Surface‐enhanced Raman spectroscopy (SERS) is a valuable tool to study these compounds when high fluorescence from the matrix obscures the Raman signal, even if a proper protocol for the extraction of the colorant is needed.